Enhanced Terahertz Wave Generation via Stokes Wave Recycling in Non-Synchronously Picosecond Pulse Pumped Terahertz Source - Chao Yan; Degang Xu; Yuye Wang; Zhaohua Wang; Zhiyi Wei; Longhuang Tang; Yixin He; Jining Li; Kai Zhong; Wei Shi; Jianquan Yao (IEEE Photonics Journal, 2019)
Enhanced terahertz wave generation via Stokes wave recycling in a non-synchronously picosecond pulse pump configuration has been demonstrated. It is theoretically analyzed that under the condition of high pump peak power density, the oscillation of the strong 1st order Stokes wave could benefit the higher order Stokes wave emission and terahertz wave generation. In the experiment, 5.71 times enhancement of terahertz wave generation was obtained via Stokes wave recycling in the non-synchronously picosecond pulse pumped terahertz parametric generator compared with the conventional single-pass terahertz parametric generation. The maximum terahertz wave average power was 61.7 μW under the pump power of 20 W and the cavity length of 170 mm, while the maximum power conversion efficiency was 3.085 × 10−6.